Development crisis of rejection transplant on a background of leucopenia - A. A. Korzenewsky; N. P. Korzhenevskaya; R. J. Nagaev (Трансплантология (Москва))
The patient in the remote period after cadaveric kidney allotransplantation developed leukopenia, which required a dose reduction of immunosuppressive drugs. The transplant rejection crisis developed against this background. Thus, the presence of leukopenia in a patient after cadaveric kidney allograft transplantation requires detecting early signs ofnot only infectious complications, but also a crisis of rejection.